Association between dietary inflammation index and malnutrition status in peritoneal dialysis patients: a cross-sectional study - Zhong, Jiaqian; Fan, Chuang; Li, Lin; Wang, Jiaming; Li, Huo; Bian, Zhongbo; Wang, Hao; Pei, Zhangming; Wang, Hongchao; Lu, Wenwei; Li, Juan (Frontiers in Nutrition, 2026)
ObjectiveChronic inflammation is prevalent in peritoneal dialysis (PD) patients, however, the potential impact of diet-related inflammation on PD patients has not been fully investigated. We aimed to explore the association between the Energy-adjusted dietary inflammatory index (E-DII) and malnutrition status in PD patients.MethodsA total of 147 PD patients from Shanghai Changzheng Hospital were included in this cross-sectional study. E-DII were calculated from the dietary data collected using a validated Food Frequency Questionnaire (FFQ). Malnutrition was determined according to the Malnutrition-Inflammation Score (MIS). Least absolute shrinkage and selection operator (LASSO) regression was carried out to screen the key nutrients associated with the risk of malnutrition. Univariate and multivariate logistic regression analyses were employed to explore the association between the key nutrients, E-DII and malnutrition.ResultsThe mean E-DII score was −0.367, ranging from −2.958 to 2.379. The mean duration of PD was 47.9 months. The overall prevalence of malnutrition was 48.3%. The key dietary nutrient associated with malnutrition was total fiber. In fully adjusted model, higher total fiber intake was associated with a lower risk of malnutrition in PD patients (ORtertile 3 vs. 1 = 0.29, 95% CI: 0.10–0.80, p = 0.018). Conversely, a higher E-DII score was associated with a higher risk of malnutrition (ORtertile 3 vs. 1 = 3.64, 95% CI: 1.25–10.64, p = 0.018).ConclusionDiets high in total fiber were associated with a reduced risk of malnutrition in PD patients. On the other hand, pro-inflammatory diets are associated with an increased risk of malnutrition in PD patients. Further studies are needed to validate and develop strategies to reduce the dietary inflammatory burden in PD patients.